Effects of 5-azacytidine and trichostatin A on dendritic cell maturation - Stepanek, I; Indrova, M; Bieblova, J; Fucikova, J; Spisek, R; Bubenik, J; Reinis, M (Journal of biological regulators and homeostatic agents, 2011)
Maturation of dendritic cells (DC) towards functional antigen-presenting cells is a complex process, the regulation of which may also involve epigenetic mechanisms. Thus, it is of interest to investigate how gene expression changes during DC maturation can be influenced with epigenetic agents, such as DNA methyltransferase or histone deacetylase inhibitors. Here, we document the effects of DNA methyltransferase inhibitor 5-azacytidine (5AC) and histone deacetylase inhibitor trichostatin A (TSA) on the murine bone marrow-derived, as well as on the human monocyte-derived DC maturation. The major impact of 5AC and TSA on the DC maturation process consisted in the inhibition of unmethylated CpG oligodeoxynucleotide (CpG ODN) 1826 or LPS-induced activation of pro- and anti-inflammatory cytokine gene expression activation. In the in vitro studies, TSA but not 5AC significantly reduced the capacity of the peptide-pulsed DC to induce total spleen as well as CD8(+) or CD4(+) cell proliferation. IFNγ production by the specific CD4(+) spleen cells co-cultured with TSA- but not with 5AC-treated DC was lower, as compared to the cytokine production after co-cultivation with untreated mature DC. Collectively, these results demonstrate the potential of epigenetic agents, which are under intensive investigation as promising anti-tumour agents, to hamper the immune response induction through their inhibitory effects on DC.
Keywords: DNA Methylation; Male; metylace DNA; cytokiny; buněčná diferenciace; molekulární sekvence - údaje; Amino Acid Sequence; Histone Deacetylase Inhibitors; Azacitidine; mužské pohlaví; dendritické buňky; azacytidin; Hydroxamic Acids; CD4-Positive T-Lymphocytes; Animals; lidé; inhibitory histondeacetylas; Humans; zvířata; kyseliny hydroxamové; myši inbrední C57BL; sekvence aminokyselin; myši; Mice, Inbred C57BL; Molecular Sequence Data; Cytokines; Dendritic Cells; Mice; CD4-pozitivní T-lymfocyty; Cell Differentiation